Effect of zircon surface coating on alumina grog and its influences on the properties of low‐cement castables. Issue 1 (5th October 2021) - Krishnan, M.; Manikandan, R.; Thenmuhil, D.
Abstract: In this investigation, four types of low‐cement castables (LCC) were prepared with sintered mullite, high alumina grog, unfired, and fired zircon coated on alumina grog. These castables were evaluated in terms of their physical, thermal, and thermomechanical properties. The castables prepared using sintered mullite showed good physical and thermal properties with higher TSR than castables with fired zircon coated on alumina grog due to higher mullite with lower anorthite phases. Fired zircon coated on alumina grog castables were superior with lower corrosion and higher TSR of castables to those of castables with unfired zircon coated on alumina grog and high alumina grog due to formation of zircon and zirconia phases and surface coated on alumina grog gave better corrosion resistance. Castables prepared using unfired zircon coated on alumina grog and high alumina grog showed poorer properties than the other castables due to formation of higher porosity of alumina grog.